2006
DOI: 10.1097/01.mpa.0000240275.68279.13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Roles of Increased Populations of Foxp3+CD4+ T Cells in Peripheral Blood from Advanced Pancreatic Cancer Patients

Abstract: Foxp3CD4 T cells are good markers for metastasis detection in PC patients and more accurate than other conventional tumor markers, especially at advanced stages of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 15 publications
5
62
0
Order By: Relevance
“…We previously showed that Foxp3 + Treg populations in peripheral blood can reflect the pathological aggressiveness of pancreatic ductal carcinomas and IPMNs (4,12). The numbers of Foxp3 + T cells were found to be increased in immune cells infiltrating pancreatic cancers and in draining lymph nodes (7,22), however, the mechanism by which Foxp3+Treg populations are expanded in peripheral blood from the tumor environment remained unclear (23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that Foxp3 + Treg populations in peripheral blood can reflect the pathological aggressiveness of pancreatic ductal carcinomas and IPMNs (4,12). The numbers of Foxp3 + T cells were found to be increased in immune cells infiltrating pancreatic cancers and in draining lymph nodes (7,22), however, the mechanism by which Foxp3+Treg populations are expanded in peripheral blood from the tumor environment remained unclear (23).…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were withdrawn from patients at the time of normal laboratory testing and before any treatment, including surgery and radiation and/or chemotherapy. T cells populations were analyzed by FACScan, as described (4,5). Briefly, peripheral blood mononuclear cells were isolated from these samples by centrifugation of 2 ml blood plus 4 ml Lymphoprep™ (AXIS-SHIELD, Oslo, Norway) at 1,800 rpm for 20 min at room temperature, after hematolysis of red blood cells with 4 ml 0.9% NH 4 Cl.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…114 On the other hand, Hiraoka reported that the prevalence of CD4 + Foxp3 + T cells, infiltrating pancreatic cancer tissue and regional lymph nodes, increases during the progression of this tumor, ranging from precursor lesions, such as PanINs and intraductal-papillary mucinous neoplasia, to invasive carcinoma. A high prevalence of these Treg subsets predicts a poor prognosis.…”
Section: Immune Response In Patients With Pancreatic Carcinoma: Role mentioning
confidence: 99%